Research on junction temperature detection method of power electronic devices based on turn-off time and turn-off loss - Lingfeng Shao (Elsevier, 2022)
The temperature-sensitive electrical parameter (TSEP) method is widely used in the extraction and prediction of junction temperature (Tj) of power semiconductor devices. In this paper, turn-off loss (Eoff) and turn-off time (toff) are taken as temperature-sensitive electrical parameters. It is proved that the junction temperature of the insulated-gate bipolar transistor (IGBT) changes abruptly during switching. The common defects of a single temperature-sensitive electrical parameter, including collector current requirements and poor junction detection accuracy, are considered. Therefore, after proving the linear relationship between junction temperature, turn-off time, and turn-off loss, a hybrid model based on turn-off loss (Eoff) and turn-off time (toff) is proposed to accurately extract junction temperature. The experimental results show that this method has the advantages of high precision and strong anti-jamming ability.